IMPLEMENTASI PENILAIAN OTENTIK ASPEK SIKAP DALAM PEMBELAJARAN GEOGRAFI DI SMA NEGERI SE-KOTA PADANG PANJANG - tika, weni nes; Anwar, Syafri (JURNAL BUANA, 2023)
This study aims to determine (1) application of authentic assessment of attitude aspects in geography learning in State High School throughout Padang Panjang (2) Implementasi of authentic assessment of attitude aspects of geography learning in Public High School of Padang Panjang (3) Difficulties of teachers in applying authentic assessment of attitude aspects in Geography learning in Public High School of Padang Panjang (4) the solution in overcoming the difficulties of teachers in applying authentic assessment of attitude aspects in Geography learning in Public High School of Padang Panjang. The research method used in this research is descriptive quantitative method. The population is 7 geography teachers and 12 11th grade students in Padang Panjang City. While the sample is taken by purposive sampling. Data collection technique using a questionnaire. Quantitative data analysisi technique is statistical-descriptive analysis. The results of study are as follows (1) the application of authentic assessment of aspects of social and spiritual attitudes is carried out very well (2) the implementation of authentic assement of aspects of spiritual attitudes in geography learning is 58% in the very good category and the assessment of social attitudes is 42% in the good category (3) the difficulty of teachers is the lack of time in conducting attitude assessment (4) the solutation in overcoming the difficulties is that the teachers collaborates with peers and the teacher must be able to divide the time.